Spatio-Temporal Variation of the Surface Urban Heat and Cool Island in Sulaymaniyah City; Land Use\Cover Change Implications - Ahmad, Prof. Dr. Soran Hamaamin; Student), A.L. Hero Nasraldin Mohammed Amin (PhD (Sulaimani Journal for Humanities, 2023)
The present study assesses the spatial and temporal patterns of the surface urban heat island (SUHI) and surface urban cool island (SUCI) in the Sulaymaniyah urban area with stating the implications of land use\land cover change between 1992 to 2022. Urban and non-urban land cover characteristics usually results with a positive difference in surface temperatures and is referred to as the urban heat island (UHI). The study depended on Landsat images as the most common data used due to its long history of space-based data collection at a global scale, the objective of this study is to investigate the changes of land surface temperature (LST) and the nature of SUHI and SUCI in the overall study area and present the samples that contribute land surface temperature change in different years, the study depended on using polygon and pixel samples to establish land use\ cover change effect on land surface temperature across this time period. For this purpose, the normalized ratio scale (NRS) proposed to adjust the LST acquired at different years to make them comparable to each other. Twenty satellite images acquired by Landsat 5, 8 and 9 which used to retrieve LST and Normalized Differences Vegetation Index (NDVI) for the study periods. The results indicate that the city experienced urban cool island comparing to the 7 km distance buffer zone in all periods, land cover pixels that changed from bare to water and bare to grass experienced most decreasing of LST with -10°C and -8°C respectively, while the most increased LST recorded with water, grass and forest to bare pixel, which was +14°C.
Keywords: LST; MonoWindow Algorithm; SUHI; SUCI; LUCC